1995
DOI: 10.1136/jnnp.58.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic orbital inflammation (orbital inflammatory pseudotumour): an unusual cause of transient ischaemic attack.

Abstract: A patient with idiopathic inflammation of the right orbit, established by biopsy, developed episodes of transient left sensorimotor hemiparesis. Neuroimaging showed intracranial extension of the disease with pronounced narrowing of the right internal carotid artery in its intracavernous portion. Oral cyclophosphamide induced gradual improvement. Transient ischaemic attack is rarely found in association with orbital disease and indicates possible intracranial extension. (J Neurol Neurosurg Psychiatry 1995;58:88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…Apart from our Case 1, there is one further case report in the literature of carotid narrowing in IIPO proven by angiography [2].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Apart from our Case 1, there is one further case report in the literature of carotid narrowing in IIPO proven by angiography [2].…”
Section: Discussionmentioning
confidence: 92%
“…Intracranial expansion as in Case 1 through the superior orbital fissure is known. To date only 19 cases of extraorbital IIPO have been reported [2]. Retro-orbital THS is characterised by inflammatory infiltration of the sinus cavernosus and/or the superior orbital fissure [7].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, there is a temporal sequence of events that demonstrates that the inflammatory process initiates within the orbit and then spills over adjacent structures. Kaye et al 7 and Borruat et al 12 adequately document in their case study that inflammation was originally confined to the orbital contents and extended with time beyond the orbit. In the cases reported by Frohman et al 2 and De Jesús et al, 13 the authors suggested that when more extensive orbital disease was seen compared with the extraorbital inflammation, its origin was probably within the orbit.…”
Section: Discussionmentioning
confidence: 95%
“…4 -7 To date, up to 15 patients with IOI have been reported with intracranial involvement (Table 1). 2,3,[5][6][7][8][9][10][11][12][13] In the vast majority of patients with idiopathic orbital and extraorbital inflammation, the cranial cavity or sinuses are usually involved (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…El compromiso externo (compresivo) es raro, siendo pocas las causas reportadas que han causado un IL destacando por frecuencia las neoplasias de cabeza y cuello (meningioma, adenoma de hipófisis, histiocitoma fibrosos y neurilemoma del X nervio craneal) (9,10) , la trombosis del seno cavernoso (11) y la mucormicosis rino-orbito-cerebral (12) ; casi todas ellas comprometiendo a la ACI en su segmento intracavernoso. Existen escasos reportes de la EIOI como causa de enfermedad cerebrovascular (accidente isquémico transitorio o infarto cerebral) por compresión de la ACI (13,14,15) . Se realizó una búsqueda bibliográfica en Medline usando los términos "orbital pseudotumor", "idiopathic orbital inflammatory disease", "idiopathic orbital inflammation", "cerebral infarction", "ischemic stroke", "watershed infarction" y "borderzone infarct"; y en Lilacs y Scielo usando los términos "seudotumor orbiFigura 2.…”
Section: Discussionunclassified